Clinical Aspects of a Rare Disease: Bardet Biedl Syndrome - Ina Ofelia FOCSA; Magdalena BUDISTEANU; Cristina STOICA; Florina NEDELEA; Claudia JURCA; Lavinia CABA; Lacramioara BUTNARIU; Monica PANZARU; Cristina RUSU; Mihaela BALGRADEAN (Modern Medicine)
Bardet Biedl syndrome (BBS) is a rare primary ciliopathy with a complex and extremely variable clinical presentation. The core features of the disease are rod-cone dystrophy, postaxial polydactyly, central obesity, urogenital anomalies, learning difficulties and kidney disease, however the impairment of any organ may complicate the clinical picture. Here we report on clinical findings of 25 patients diagnosed with BBS. Our study is the first on a cohort of Romanian BBS patients, aiming to emphasize the complexity of the disease that may have a devastating impact on patients and their families. Thus, an early clinical diagnosis is crucial for anticipation of other system and organ involvement. Periodic follow up, by a multidisciplinary team, may prevent several severe complications, which could accelerate or aggravate the most deleterious aspects of the disease: loss of vision or renal impairment.